A 2D cell segmentation protocol for monitoring multiple STAT signaling pathways by fluorescence microscopy - Gergő Szanda; Éva Wisniewski; László Barna; Gábor Turu; Ken Mackie (STAR Protocols)
Summary: Microscopic cell segmentation typically requires complex imaging, staining, and computational steps to achieve acceptable consistency. Here, we describe a protocol for the high-fidelity segmentation of the nucleus and cytoplasm in cell culture and apply it to monitor interferon-induced signal transducer and activator of transcription (STAT) signaling. We provide guidelines for sample preparation, image acquisition, and segmentation. The approach performs indistinguishably from neural-network-based segmentation while requiring only conventional and cost-effective techniques. The protocol can be adapted to other signaling molecules undergoing nucleo-cytoplasmic shuttling and to high-throughput applications.This protocol enables simultaneous monitoring of two STAT isoforms using only conventional techniques and equipment and improves upon the assay published in Szanda et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.